Analisis Perpustakaan Sekolah SDK Maria Fatima Bangkalan Sebagai Penunjang Gerakan Literasi - Kehi, Albertina Noviana; Citrawati, Tyasmiarni (JOURNAL OF EDUCATION FOR ALL, 2024)
The aim of the research is to find out the program implemented in the SDK Maria Fatima Bangkalan school library to support the literacy movement and to find out the form of implementation of the school literacy movement at SDK Maria Fatima Bangkalan. this research uses descriptive qualititative. The data collection techniques used were observation, interviews and documentation. The result of this research show that the SDK Maria Fatima Bangkalan school library is very important fo the school community to support the school literacy movement, however the implementation process has not been carried out a optimally as possible and is less than optimal. Despite this, the implementation of the SDK Maria Fatima Bangkalan school library as a support for the literacy movement has gone quite well. However, there are alsa obstacles in the SDK Maria Fatima Bangkalan school library as a literacy movement, including the lack of visits to the library by school resident, the absence of library administration, and the literacy movement implementation program is not yet optimal, such ads the reading corner program has not been used well by student. Therefore, efforts are needed in school library management and school principals to overcome problems in school libraries and the literacy movement experienced, including increasing insight into managing school libraries, collaborating, and discussing with teachers regarding school libraries in supporting the literacy movement to achieve its goals. From the school library as supporting the school literacy movement can be achieved.